Investigating the Contribution of Mature Collagen Crosslinks to Cooked Meat Toughness Using a Stewed Beef Shank Model - W. Wu; A. A. Welter; C. K. Chun; T. G. O'Quinn; G. Magnin-Bissel; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective: The objective of this study was to investigate mature collagen crosslink densities and their relationship to connective tissue texture using a stewed beef shank model. Study Description:Connective tissue texture, Warner-Bratzler shear force, and collagen content and characteristics were measured for six different beef shank cuts from eight U.S. Department of Agriculture Low Choice beef carcasses (n = 48). Results: Deep digital flexor from the foreshankhad the toughest connective tissue texture, greatest Warner-Bratzler shear force value, most cooked collagen content, one of the greatest insoluble collagen percentages, as well as greatest raw and cooked pyridinoline densities among all the beef shank cuts (P<0.05). Correlation analysis showed that cooked collagen content, percent insoluble collagen, as well as raw pyridinoline densities had positive correlations with connective tissue texture (r = 0.550, 0.498, and 0.560, respectively;P<0.01) and Warner-Bratzler shear force (r = 0.615, 0.392 and 0.730, respectively;P<0.05). The Bottom Line:Pyridinoline is a heat stable collagen crosslink that is difficult to degrade even with extensive heat treatment. As a result, raw pyridinoline density is a good indicator for heat insoluble collagen content, cooked beef connective tissue texture, and ultimately, tenderness in beef cuts with high concentration of connective tissue prepared with moist heat cookery.
Keywords: beef shank; insoluble collagen; pyridinoline